2012
DOI: 10.1021/ja300827t
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Elimination from Arylpalladium Cyanide Complexes

Abstract: We report the isolation and characterization of arylpalladium cyanide complexes that undergo reductive elimination to form arylnitriles. The rates of reductive elimination from a series of arylpalladium cyanide complexes reveal that the electronic effects on the reductive elimination from arylpalladium cyanide complexes are distinct from those on reductive reductive eliminations from arylpalladium alkoxo, amido, thiolate, and enolate complexes. Arylpalladium cyanide complexes containing aryl ligands with elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Recently, Hartwig showed that reductive elimination to form ArCN is slower for electron-deficient aryl groups. [25] That a catalyst based on the larger ligand L2 allows for more facile reductive elimination for electron-deficient substrates is in accord with this view. This method exhibits high tolerance for substrates bearing free N–H or O–H groups, such as primary amides ( 1g ), sulfonamides ( 1h ), anilines ( 1j ), and benzylic alcohols ( 1j ), all of which could be converted to the corresponding benzonitrile using less than 1 mol % Pd.…”
mentioning
confidence: 86%
“…Recently, Hartwig showed that reductive elimination to form ArCN is slower for electron-deficient aryl groups. [25] That a catalyst based on the larger ligand L2 allows for more facile reductive elimination for electron-deficient substrates is in accord with this view. This method exhibits high tolerance for substrates bearing free N–H or O–H groups, such as primary amides ( 1g ), sulfonamides ( 1h ), anilines ( 1j ), and benzylic alcohols ( 1j ), all of which could be converted to the corresponding benzonitrile using less than 1 mol % Pd.…”
mentioning
confidence: 86%
“…The conversions of the latter substrates were not improved even upon extending the reaction time from 2 h to one day with the sole exception of 4-chloro-1-bromobenzene (7g), for which the conversion to 8g increased from less than 5% to 10% (note: the corresponding amides, possibly resulting from hydrolysis of the nitriles, were detected in only negligible amounts). This striking difference noted for the two classes of substrates may reflect changes in the reaction energetics (reductive elimination of ArCN is slower for electron-poor aryl groups [26]) and also a relatively low stability of the formed catalyst. changes in the reaction energetics (reductive elimination of ArCN is slower for electron-poor aryl groups [26]) and also a relatively low stability of the formed catalyst.…”
Section: Pd-catalyzed Cyanation Of Aryl Bromidesmentioning
confidence: 99%
“…This striking difference noted for the two classes of substrates may reflect changes in the reaction energetics (reductive elimination of ArCN is slower for electron-poor aryl groups [26]) and also a relatively low stability of the formed catalyst. changes in the reaction energetics (reductive elimination of ArCN is slower for electron-poor aryl groups [26]) and also a relatively low stability of the formed catalyst. In summary, the newly synthesized hydrophilic phosphinobiphenyl ligand L2 afforded less stable and less efficient catalysts for the Pd-catalyzed cyanation of aryl bromides with K4[Fe(CN)6] in 1,4-dioxane-water mixtures than its less sterically congested isomer L1.…”
Section: Pd-catalyzed Cyanation Of Aryl Bromidesmentioning
confidence: 99%
“…Notably, silyl-bridged directing groups were used owing to their ease installation/removal and modification. [4,9] Accordingly,w ee xamined fluorinated pyridyl directing groups (as in 3 and 4)and an improved yield relative to the parent pyridyl-based directing group was obtained. Upon transmetalation of the cyanide ion, the palladium metal center is expected to be more electron dense and therefore,t he appropriate pacidic ligand is required to stabilize the short-lived intermediate.…”
mentioning
confidence: 97%
“…[2] In this regard, meta-a nd paraselective CÀHb ond activation of aromatic arenes stand as worthy examples. [3][4][5] Recently, meta-C À Ha lkylation and alkenylation have been achieved with the aid of strong coordinating pyrimidine-based template. [3][4][5] Recently, meta-C À Ha lkylation and alkenylation have been achieved with the aid of strong coordinating pyrimidine-based template.…”
mentioning
confidence: 99%